Strategi Peningkatan Efektivitas Penagihan Piutang PBB melalui Pendampingan Aparatur di Bapenda Kabupaten Tapanuli Utara - Bonifasius H. Tambunan; Aldi Sitorus; Mula Simatupang; Alda Rajagukguk; Surya Agafie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service initiative addresses the outstanding Land and Building Tax (PBB) receivables at the Regional Revenue Agency (BAPENDA) of North Tapanuli Regency, which has become a significant obstacle to optimizing Regional Original Revenue (PAD) realization. The initiative aims to identify factors hindering PBB receivable collection effectiveness, analyze critical points of prevailing issues, and formulate applicable strategies to enhance collection performance. Methods employed include field observations, technical staff mentoring, and arrears data analysis using Excel software. Findings indicate that collection process barriers are influenced by two primary factors: internal and external. Internal factors include limited human resources, lack of integrated database systems, and inadequate information technology infrastructure. External factors encompass community socio-economic conditions, geographical constraints, and low taxpayer legal awareness. Based on these findings, several strategic measures are recommended: strengthening information systems and databases, enhancing personnel capacity, implementing public education programs, and optimizing inter-agency coordination. Implementation of these strategies is expected to reduce PBB receivables and improve regional financial management accountability.